Analysis Of The Application Of Regional Financial Accounting Systems At The Regional Financial And Asset Management Agency Of Medan City - Jihan Reswita; Rahmat Daim Harahap (BADAN PENERBIT STIEPARI PRESS, 2024)
This study aims to evaluate the application of government accounting system in accordance with Permendagri No. 13 of 2006 and PP No. 24 of 2005. The data was obtained through interviews and documentation from the Regional Finance and Asset Management Agency (BPKAD) of Medan City. The analysis method used is qualitative descriptive, which aims to understand the implementation of the government accounting system in BPKAD Medan City. The results showed that BPKAD Medan City has implemented a government accounting system in accordance with applicable regulations.